Solidariedade social tributária na perspectiva da teoria tridimensional do direito de Miguel Reale - Contipelli, Ernani de Paula (2009)
The proposal of this work is focused on the analysis of social solidarity value and its axiological developments at the framework of the tributary normative system, using as theoretical basis of the questions the Law‟s Tridimensional Theory by Miguel Reale. Initially, I intend to show the essential concepts for understanding the Law‟s Tridimensional Theory designed by Miguel Reale, which leads to the foundations of its ontology and axiology, that finds its nucleus on the value source of the human being in its historic and cultural perspective, as well as on the way of integration between the constitutive elements of legal experience. Once is structured the philosophic foundation of the thesis, it goes to analyze the social solidarity value on its historical contextualization, towards the recognition of the evolution of its meaning over time, to subsequently check its axiological content and its relationship with other values linked to the human person, taking into account the theoretical concepts of Miguel Reale. Besides, I will show social solidarity value as constant or invariant axiological determinant of the formula for ideological integration of the model of the Democratic State of Law described on the constitutional normative complex, that influences the validity of the legal enactment process, as well as the construction of significance of their models, acting in tax normative system, for correlate the duty of collaboration of the community member to pay tax with the right of require for the (or duty of) State of redistribute properly the received riches. Finally, the aim is to consider the axiological effects of the social solidarity directions in the structuring elements of the tax normative system, presenting your decisive penetration in the exercise of the tax powers expressed on the Federal Constitution, determining the necessary relation of reciprocity implication with the ideals reflected in the general principles of the tax law, especially, the contributive ability and the linking of the financial resources